POTENCY OF PREDATOR (Menochilus sexmaculatus) AUGMENTATION FOR WHITE FLY (Bemisia tabaci) MANAGEMENT AND ITS EFFECT ON GEMINI VIRUS INFESTATION ON TOMATO - Setiawati, W.; Gunaeni, N.; Uhan, T. S.; Hasyim, A. (Indonesian Journal of Agricultural Science, 2012)
Bemisia tabaci (Gen.) (Homoptera: Aleyrodidae) is one of the most serious pests on tomato. It is mainly controlled by chemi-cal means, requiring some 25 sprays during the average growing season. The extensive and repeated use of insecticides has dis-rupted the natural balance between this pest and its natural enemies. In this study, Menochilus sexmaculatus F. was evalu-ated as a possible biological control agent of B. tabaci and its effect on Gemini virus infestation. The study was conducted at the experimental station of the Indonesian Vegetables Research Institute (IVeGRI) in Lembang, West Java (1,250 m above sea level) from August to December 2008. The experimental plots consisted of 0.35 ha of tomato (Â± 100 m2 per plot) and spatially separated with four rows of maize (a minimum of 1 m) inter-plot distance to prevent cross-contamination among plots. The experiment was arranged in completely randomized block design with eight treatments and four replications. M. sexmaculatus were released at 24 days after planting. The treatments were designed according dosages and schedules at three released populations (i.e. 10 predators per plot, 20 predators per plot, and 10 predators per plot at vegetative stage followed by 20 predators per plot at generative stage); two places of release (center and edge of the plot); and two schedules of release (weekly and biweekly). Efficacy of the predator was measured in terms of the density of B. tabaci, both before and after release of the predator and its effect on Gemini virus infestation. The result indicated the potential use of M. sexmaculatus to control B. tabaci and its effect on Gemini virus infestation on tomato. Reductions in B. tabaci populations and subsequent tomato yields were significant. B. tabaci population in plots receiving 10 predators showed 73.62% and 75.75% reductions by the end of experiment. The incidence and intensity of Gemini virus were consistently and significantly lowest and tomato yield gain was observed when 10 predators were released at weekly intervals. It is suggested that release of M. sexmaculatus against B. tabaci on tomato may be offered as an alternative solution to increase implementation of biologically-based B. tabaci management.